Whole cluster and dried stem additions effects on chemical and sensory properties of Pinot Noir wines over two vintages - Casassa, Luis Federico (2020)
The effect of whole cluster at 50% (50% WC) and 100% additions (100% WC), as well as that of Dried stems (DS) on Pinot noir wines from the Edna Valley AVA of California (USA) were investigated over two consecutive vintages at commercial scale. Additions of 100% WC led to significant increases in pH and volatile acidity. Anthocyanins, polymeric pigments, and color were more influenced by vintage than by the winemaking treatments, but in the case of 100% WC wines, they were either unaffected or negatively affected. Conversely, the tannin content of the wines increased more or less proportional to the percentage of whole clusters and stems added, that is, 68% (50% WC), 100% (100% WC) and 90% (DS) in 2016 and 61% (50% WC), 123% (100% WC) and 137% (DS) in 2017, relative to Control (C) wines. GC-MS data showed higher relative levels of ethyl cinnamate and benzaldehyde in 100% WC wines and relative abundance of esters in DS wines. Descriptive sensory analysis showed that 100% WC additions led to vegetal, cooked fruit flavors and spicy (clove) notes, whereas DS additions produced wines that were more herbal, fruity and astringent, with lifted fruity notes related to esters, and astringency sensations related to enhanced tannin extraction from the stems. Both whole clusters and dried stem additions led to variable increases in perceived astringency, suggesting that they can be used to add mouthfeel and improve texture in Pinot noir wines.